Also here: Wikipedia

]]>Typically, you shift the original function into a form

f(x) = (x+a)²+b

It does no matter that the function equal to any given value, because the equation formed can be easily solved.

f(x)=c

(x+a)²=c-b

hence

Actually, given a equation of standard form, the explicit solution fomula is derived by this procedure

ax²+bx+c=0

a(x+b/2a)²=b²/4-c

......

I've just been revising some of my earlier a-level work and I'm a little confused with this:

"Let f(x) = x^2 + 6x + 7.

(a) Put f(x) into completed square form.

(b) Solve the equation f(x) = 4."

I do know how to do all of this but I can't for the life of me see where they are getting f(x) = 4 from?!

]]>